Salam Crowdfunding Innovation as an Alternative to Sharia-Based Agricultural Financing in the Digital Era - Nailus Sa'adah; Rafif Hawari; Amani Mardhatila (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
The development of Islamic financial technology opens up new opportunities to strengthen financing in the agricultural sector, especially through the use of salam contracts that are classically used as pre-harvest instruments. This article analyzes how the DSN-MUI fatwa and the Financial Services Authority (OJK) regulations shape the legality framework and operational structure of greeting based crowdfunding in the digital ecosystem. This research uses a literature study approach with an analysis of the doctrine of fiqh provisions, Fatwa No. 05/DSN-MUI/IV/2000 and Fatwa No. 117/DSN-MUI/II/2018, as well as OJK regulations related to financial technology services and sharia escrow. The results show that the legality of this model relies heavily on the harmonization between classic greeting principles such as full upfront payment obligations, certainty of commodity specifications, and scheduled deliveries with a digital architecture that requires the use of escrow, e-contracts, and data protection mechanisms. In addition, the effectiveness of the salam crowdfunding model is greatly influenced by the design of risk mitigation through takaful, escrow, and third party guarantee options that do not conflict with sharia principles. This study concludes that greetings crowdfunding can be a legitimate, efficient, and sustainable agricultural financing instrument if legal structures, operational flows, and risk mitigation schemes are designed in accordance with the provisions of fiqh and national regulations.